2001
DOI: 10.1097/00006123-200111000-00010
|View full text |Cite
|
Sign up to set email alerts
|

Serum S100B Protein Levels Are Correlated with Subclinical Neurocognitive Declines after Carotid Endarterectomy

Abstract: These data suggest that subtle cerebral injuries after CEA, even in the absence of overt strokes, are associated with significant increases in serum S100B but not neuron-specific enolase levels. Analyses of earlier time points in future studies of subtle cognitive injuries and biochemical markers of cerebral injury after CEA may be revealing.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
23
0
1

Year Published

2007
2007
2021
2021

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 39 publications
(26 citation statements)
references
References 31 publications
2
23
0
1
Order By: Relevance
“…However, this study is the first to evaluate NLR in a cohort of patients undergoing CEA and to determine whether NLR is predictive of cognitive dysfunction. Cognitive dysfunction, though less clinically momentous than stroke, has been associated with markers of brain injury 3 and mortality 4 .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, this study is the first to evaluate NLR in a cohort of patients undergoing CEA and to determine whether NLR is predictive of cognitive dysfunction. Cognitive dysfunction, though less clinically momentous than stroke, has been associated with markers of brain injury 3 and mortality 4 .…”
Section: Discussionmentioning
confidence: 99%
“…Although the incidence of stroke during the perioperative period of CEA is 3–5%, a subtler form of neurologic injury, cognitive dysfunction, is exhibited in approximately 25% of patients 1 day after CEA 1, 2 . Cognitive dysfunction has been associated with markers of brain injury 3 and earlier retirement and mortality 4 . While the underlying cause of the cognitive dysfunction is likely multifactorial, previous studies suggest that systemic inflammation plays an important role 59 .…”
Section: Introductionmentioning
confidence: 99%
“…Previous work has demonstrated that patients with cognitive dysfunction have significantly elevated markers of neuronal injury(17), reduced quality of life, and early mortality(16) following surgery. Therefore, TCD assessment of MCA–MV during CEA may be an appropriate approach to reducing the risk of cognitive dysfunction after surgery and further improving the safety of CEA.…”
Section: Discussionmentioning
confidence: 99%
“…Though less clinically momentous than stroke, postoperative cognitive dysfunction has significant implications for quality of life and early mortality(16). Glial markers of neuronal injury are significantly elevated in CEA patients that exhibit cognitive dysfunction as early as 24 hours after CEA(17). In our previous work, we documented that approximately a quarter of CEA patients exhibit cognitive dysfunction 24 hours after CEA(18, 19).…”
Section: Introductionmentioning
confidence: 99%
“…Approximately a quarter of CEA patients demonstrate eCD 24hrs after CEA 8, 9 . It is a subtler form of neurologic injury than stroke and is similar to stroke in its pathophysiology; patients with eCD demonstrate significantly elevated markers of neuronal injury 10 as well as asymmetric cerebral blood flow on magnetic resonance perfusion brain scans 11 .…”
Section: Introductionmentioning
confidence: 99%